Acute kidney disease in mice is associated with early cardiovascular dysfunction - Pauline Caillard; Youssef Bennis; Cédric Boudot; Denis Chatelain; Pierre Rybarczyk; Agnès Boullier; Sabrina Poirot; Dimitri Titeca-Beauport; Sandra Bodeau; Gabriel Choukroun; Saïd Kamel; Isabelle Six; et al. (Renal Failure)
Acute kidney injury (AKI) and chronic kidney disease (CKD) are major health concerns due to their increasing incidence and high mortality. They are interconnected syndromes; AKI without recovery evolves into acute kidney disease (AKD), which can indicate an AKI-to-CKD transition. Both AKI and CKD are associated with a risk of long-term cardiovascular complications, but whether vascular and cardiac dysfunctions can occur as early as the AKD period has not been studied extensively. In a mouse model of kidney injury (KI) with non-recovery, we performed vasoreactivity and echocardiography analyses on days 15 (D15) and 45 (D45) after KI. We determined the concentrations of two major gut-derived protein-bound uremic toxins known to induce cardiovascular toxicity—indoxyl sulfate (IS) and para-cresyl sulfate (PCS)—and the levels of inflammation and contraction markers on D7, D15, and D45. Mice with KI showed acute tubular and interstitial kidney lesions on D7 and D15 and chronic glomerulosclerosis on D45. They showed significant impairment of aorta relaxation and systolic-diastolic heart function, both on D15 and D45. Such dysfunction was associated with downregulation of the expression of two contractile proteins, αSMA and SERCA2a, with a more pronounced effect on D15 than on D45. KI was also followed by a rapid increase in IS and PCS serum concentrations and the expression induction of pro-inflammatory cytokines and endothelial adhesion molecules in serum and cardiovascular tissues. Therefore, these results highlight that AKD leads to early cardiac and vascular dysfunctions. How these dysfunctions could be managed to prevent cardiovascular events deserves further study.